Answer:
![\left(\frac53,(14)/(3)\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vs4et12has2v7o30tissxhugi2d0bk9lp1.png)
Explanation:
Equation 1: y = 4x - 2
Equation 2: y = x + 3
Subtract Equation 2 from Equation 1 and solve for x:
⇒ 0 = 3x -5
⇒ 3x = 5
⇒ x = 5/3
Substitute found value of x into one of the equations and solve for y:
⇒ y = 5/3 + 3
⇒ y = 14/3
Therefore, the solution of the system of equations is:
![\left(\frac53,(14)/(3)\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vs4et12has2v7o30tissxhugi2d0bk9lp1.png)